The Influence Of Tiktok Avoskin’s Social Media Marketing Activity On Customer Purchase Intention - Syafira Luthfi Hanifah; Anas Hidayat (International Journal of Economics, Business and Innovation Research, 2024)
Technology has now developed rapidly and reaches various aspects of life, one of which is the activity of buying and selling products. Now the internet has emerged which has created various digital social media platforms which are currently mostly used by entrepreneurs to carry out product buying and selling activities. This research aims to analyze the influence social media marketing activities to purchase intention brand skincare Avoskin. This research examines social media marketing activities skincare Avoskin which is carried out on Tiktok social media. Technique convenience sampling used in this research with 252 respondents. Processing the results of this research uses quantitative methods and then the data is processed using the Smart PLS application. The results of this research show that social media marketing activities provide a positive influence on brand awareness And brand image, while against purchase intention does not have a positive influence.Brand awareness also has a positive influence on brand image And purchase intention, final brand image also has a positive influence on purchase intention.